L-band CYTOP Bragg gratings for ultrasound sensing - Broadway, Christian; Kalli, Kyriacos; Theodosiou, Antreas; Zubel, Michal; Sugden, Kate; Megret, Patrice; Caucheteur, Christophe (My University, 2018)
Polymer optical fibre (POF) has been receiving increasing attention for sensing applications. The fundamental properties of POF such as PMMA deliver at least an order of magnitude in improvements over silica fibres, though practical difficulties create additional complexity. POF has the potential to deliver lower acoustic impedance, a reduced Young's Modulus and a higher acoustic sensitivity within the megahertz region. In contrast, existing piezo-electric transducers have an inherent narrow acoustic bandwidth and a proportionality to size that causes difficulties for applications such as endoscopy within the biomedical domain. POF generally suffers high attenuation per kilometre at telecommunications wavelengths, limiting fibre lengths to mere centimetres. However, CYTOP, a graded index perfluorinated polymer, is a commercially certified product allowing the use of telecoms region technology and tens of meters of fibre without exceeding acceptable losses. With an effective refractive index between 1.32 and 1.33, it is fundamentally better placed for applications using water or a similar media for acoustic coupling. We demonstrate ultrasonic detection at 5,10 and 15 MHz using a TFBG within a CYTOP fibre in the telecoms region and the latest knowledge in POF handling and connectorisation. This first step in the use of CYTOP demonstrates the viability of the sensor and paves the way towards further advances towards its eventual application.
Keywords: Biomedical applications; CYTOP; Fibre Bragg gratings; Fibre sensors; Polymer optical fibre; Ultrasound detection